DISCOVERING POLITENESS STRATEGY IN VLADIMIR PUTIN’S SPEECH ON THE RUSSIAN-UKRAINE WAR 2022 - Dianitami, Annisa Ayu (Language Horizon: Journal of Language Studies, 2024)
The implementation of politeness strategy can be found in social interactions, such as in political speech. On February 24, 2022, Vladimir Putin delivered a speech that justified a “special military operation” in Ukraine. Putin’s communication often fails to adhere to or intentionally deviates from typical norms of politeness. The study aims to analyze politeness strategies in Vladimir Putin’s speech on the Russian-Ukraine conflict in 2022. It employed a qualitative approach and applies politeness theory by Brown and Levinson (1987) for analysis. The results revealed that Vladimir Putin employed bald-on-record, positive, negative, and off-record politeness strategies, which are divided into several variations of specific strategies. Bald-on-record is the most frequently used, followed by positive and negative, with off-record politeness being the least frequently used strategy. The bald-on-record strategy dominated Putin’s speech because he wanted to increase his efficiency in communicating rather than being long-winded and minimizing face-threatening acts (FTAs). He also had much higher power than his audience, which allowed him to give orders, commands, decisions, and even threats to his audience or political opponents.